Narrativas de construção da formação do mediador de conflitos - Carvalho, Analice de Sousa Arruda Vinhal de (2019)
The present study aimed to understand from the narratives of mediators, how the construction of training in conflict mediation takes place. The participants were four mediators with five years of professional practice. The instruments used in the data collection were the researcher herself, the semi-structured interview and the timeline. In order to understand the subjects' narratives, the narrative method of Michael White and the Corinna Schabbel timeline were used, considering structure, plot and the emotional panorama. The results showed the importance of self-knowledge and interdisciplinarity in the construction of the formation of the person (self) of the mediator.